The caudinid sea cucumbers of New Zealand (Echinodermata: Holothuroidea: Molpadida: Caudinidae) - Davey, Nicola; O’loughlin, Mark (Zootaxa, 2013)
Five species of Caudinidae occur in New Zealandwaters. Two new species are described: Paracaudina alta sp. nov.; Pa-racaudina reductia sp. nov. Two species reported previously are discussed: Paracaudina chilensis (Müller) and Paracau-dina coriacea (Hutton). A lectotype has been established for P. coriacea (Hutton). Hedingia albicans var. glabra (Théel) is raised out of synonymy with Hedingia albicans (Théel), and the variety elevated to species status as Hedingia glabra (Théel). A key is provided for theNew Zealand species of Caudinidae.